Religiosity, parties and election: Islamization and democratization in post-Soeharto Indonesia - Tanthowi, Pramono U (Indonesian Journal of Islam and Muslim Societies, 2012)
The political development in Indonesian during the first decade of reform erawitnesses a resurgence of Muslim politics, which had been facing a political impassduring the 1970s and 1980s. In contrast to current political development in theArab World, the resurgence of Muslim politics in Indonesia has been marchinghand in hand with democratization. The blossoming of tens of Islamic politicalparties by no means that they speak with a single voice. Rather, political Islam isnow represented by parties with more diverse platforms. Those parties are notonly varied in their commitment to an Islamist agenda but also strongly dividedon this agenda. Yet, they all welcome and uphold âMuslimâ aspirations. As far astheir performance in the 1999 and the 2004 elections is concerned, there was asignificant decline for Muslim politics compared to the first democratic election of1955. The results reflected the minority appeal of Islamism, regardless of boththe fact that the majority of the Indonesians are Muslims and the fact that therehas been increasing Islamic revivalism within Indonesian society.